Tracheal compression as auxiliary method in the radiologic diagnosis of the cervical tracheal collapse - Canola, Júlio Carlos; Borges, Naida Cristina (Brazilian Journal of Veterinary Research and Animal Science, 2005)
Tracheal collapse is generally a syndrome of small-breed dogs that is occasionally reported in larger breeds or other species. It is characterized by weakening and loss of adequately support dynamic intraluminal pressure changes. The diagnosis bases on the clinical signs and in the exams of ray-x, fluoroscopy, ultrasonography and tracheobronchoscopy. Forty adult small dogs of different breeds, twenty health and twenty with suspicion of that tracheal collapse. They had the cervical and thoracic areas x-rayed in lateral projections with and without ventral compression of the trachea. The light pressure in the cervical trachea was accomplished in the thoracic inlet with a "eraser pear" adapted in a glass stem during the radiographic examination. The twenty animals without abnormalities of the airways presented subtle changes in the diameter traqueal independent or not of the compression. The suspicious dogs of collapse presented or no narrowing of this organ depending on the breathing phase in that they were during the radiographic projection not allowing definitive diagnosis. However when all animals of this group were submitted to the technique of compression of the trachea they presented local narrowing of this organ characterizing tracheal collapse. The method was shown efficient, practical and safe in the diagnosis of cervical tracheal collapse. Besides to eliminate the need of x-rays in different moments of the breathing cycle and not to represent additional costs.